2011
DOI: 10.1007/978-3-642-19718-5_16
|View full text |Cite
|
Sign up to set email alerts
|

From Exponential to Polynomial-Time Security Typing via Principal Types

Abstract: Abstract. Hunt and Sands (POPL'06) studied a flow sensitive type (FST) system for multi-level security, parametric in the choice of lattice of security levels. Choosing the powerset of program variables as the security lattice yields a system which was shown to be equivalent to Amtoft and Banerjee's Hoare-style independence logic (SAS'04). Moreover, using the powerset lattice, it was shown how to derive a principal type from which all other types (for all choices of lattice) can be simply derived. Both of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…We extended the flow-sensitive type system from [HS06] to provide for each output channel individual dependency sets per point in the program and demonstrated that this is sufficient to support dynamic information flow policies. We proved the type system sound with respect to a straightforward two-run property which we showed sufficient to imply knowledge-based security conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We extended the flow-sensitive type system from [HS06] to provide for each output channel individual dependency sets per point in the program and demonstrated that this is sufficient to support dynamic information flow policies. We proved the type system sound with respect to a straightforward two-run property which we showed sufficient to imply knowledge-based security conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The original work of [HS06] defines a family of type systems, parameterised by choice of a multi-level security lattice, and establishes the existence of principal typings within this family. The later work of [HS11] defines a single system which produces only principal types.…”
Section: [Ab04] [Ar80] and [Bbl94]mentioning
confidence: 99%
“…The flow-sensitive types system was defined by a family of inference systems which is forced to satisfy a simple non-interference property. Their recent work [9] showed how flow-sensitive multi-level security typing can be achieved in polynomial time. In addition to type-based treatments of secure information flow analysis for programs, Clark et.…”
Section: Related Workmentioning
confidence: 99%
“…We rely on abstract interpretation to derive a static analysis similar to existing ones inferring dependences (Amtoft and Banerjee 2004;Hunt and Sands 2006;Amtoft et al 2006;Hunt and Sands 2011). Recall that our analyses are parametrised on a security lattice L and program P. We denote by l ; x an atomic dependence constraint, with l ∈ L and x ∈ VarP, read as "agreement up to security level l leads to agreement on x".…”
Section: Dependencesmentioning
confidence: 99%